Tokoh Pendidikan Islam Perempuan Rahmah El-Yunusiah - Asni Furoidah (FALASIFA : Jurnal Studi Keislaman, 2019)
One way to improve the lot and raise the dignity of women is through education. The first female Islamic education figure in Indonesia was Rahmah el-Yunusiyah, she was a figure of women's struggle during the physical revolution. He was born from a family with a strong religious education background. During childhood Rahmah el-Yunusiyah started school at the Diniyah School led by her brother, Zainuddin Labay, which was founded in 1915 for sons and daughters using modern learning systems and lessons. The role of Islamic education as one of the right ways to raise the degree of women has had since he was a teenager. Rahmah's belief in the role of education was realized with the establishment of the school under the name AL-Madrasah AL-Diniyyah Li Al-Banat in 1923 to attract the attention of the community especially mothers, intellectuals and groups who were very strong in holding old traditions, this newly founded school was also called Diniyyah School Poetri. Trinity education system, which is close cooperation between the school environment, dormitories, and households or the community.